2001
DOI: 10.1063/1.1419053
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-polarity dependence of Ti/Al contacts to freestanding n-GaN substrate

Abstract: The effect of crystal polarity on the electrical properties of Ti/Al contacts to n-GaN substrate has been investigated. The Ti/Al contacts prepared on Ga-face n-GaN substrate became ohmic with a contact resistivity of 2×10−5 Ω cm2 after annealing at temperatures higher than 600 °C for 30 s. On the contrary, the contacts on N-face n-GaN substrate exhibited nonlinear current–voltage curve and high Schottky barrier heights over 1 eV were measured at the same annealing conditions. These results could be explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…Figure 4a shows forward I-V characteristics of Pt Schottky contacts on both Ga-face and N-face samples. The Schottky barrier height (SBH) on the Ga-face sample was higher by 0.32 eV than that on N-face one, in good agreement with the previous results [4,8]. The reverse leakage currents at -10 V on Ga-face and N-face samples were measured to be 2.96 (±1.38) × 10 -12 A and 1.26 (±0.29) × 10 -11 A, respectively.…”
Section: Resultssupporting
confidence: 80%
“…Figure 4a shows forward I-V characteristics of Pt Schottky contacts on both Ga-face and N-face samples. The Schottky barrier height (SBH) on the Ga-face sample was higher by 0.32 eV than that on N-face one, in good agreement with the previous results [4,8]. The reverse leakage currents at -10 V on Ga-face and N-face samples were measured to be 2.96 (±1.38) × 10 -12 A and 1.26 (±0.29) × 10 -11 A, respectively.…”
Section: Resultssupporting
confidence: 80%
“…For vertical LEDs, n-ohmic contacts yield poor electrical characteristics (i.e., N-face n-GaN) [9]. Kwak et al [10] stated that Ti/Al contact on hydride vapor phase epitaxy-grown Ga-and N-face n-GaN were annealed above 500 o C, the Ga-face showed ohmic behaviors with a ρ c of ~10 -5 Ω cm 2 , but N-face contact exhibited non-ohmic behaviors. Jeon et al [11] reported that the electrical properties of TiN/Al and Ti/Al ohmic contacts to N-face n-GaN thin films prepared by a laser lift-off process were significantly degraded upon annealing at temperatures in excess of 300 o C. These results indicate that the fabrication of high-performance vertical LEDs, low ρ c and thermally stable N-face n-ohmic contacts are essential.…”
mentioning
confidence: 99%
“…The elastic proton-proton amplitude given by the one-pomeron exchange reads Figure 1: The differential proton-proton elastic cross section (left) and the local slope B (right) described by a one pomeron amplitude with a pure exponential coupling and a linear pomeron trajectory; the data are from [5]- [11]. The vertical line at −t = 0.3 GeV 2 is simply for ease of reference.…”
Section: One-pomeron Exchangementioning
confidence: 99%
“…The next step is to account for the non-enhanced multi-pomeron diagrams generated by twoparticle s-channel unitarity The differential proton-proton elastic cross section (left) and the local slope B (right) described by the one pomeron amplitude with the coupling given by the proton form factor F 1 (t), and with the pion loop included in the pomeron trajectory; the data are from [5]- [11]. The parameters are ∆ = 0.085, σ 0 = 22 mb and α P = 0.3 GeV −2 .…”
Section: Eikonal Rescatteringmentioning
confidence: 99%
See 1 more Smart Citation